Euro, the dollar and gold (World Gold Council LondonGB, 2001)
Focuses on the role of, prospects for, gold as a credit risk-free reserve asset as a potential stabiliser in a world of free-floating currencies, and across the world as a day-to-day asset of choice for billions of people.
Proceedings of the conference held in Rome on 17 November 2000